2015
DOI: 10.15171/jarcm.2015.036
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone deficiency in cleft lip and palate patients

Abstract: Citation: Abdollahi-Fakhim Sh, Bayazian Gh, Shiva S, Sohrabpour M, Ebrahimzade Y. Growth hormone deficiency in cleft lip and palate patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 15 publications
(23 reference statements)
0
6
0
3
Order By: Relevance
“…The researchers linked these findings with the concurrent embryological development of foetal oral cavity and hypophysis. They also emphasized the importance of malnutrition in this particular group of patients . In contrast; Van der Plas et al reported normal hypophysis volume on MRI despite shorter stature and slower growth rate in females with CLP.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…The researchers linked these findings with the concurrent embryological development of foetal oral cavity and hypophysis. They also emphasized the importance of malnutrition in this particular group of patients . In contrast; Van der Plas et al reported normal hypophysis volume on MRI despite shorter stature and slower growth rate in females with CLP.…”
Section: Discussionmentioning
confidence: 94%
“…Although some studies and clinical observations report that the skeletal development of CLP patients is deficient to some extent when compared to normal individuals, some researchers suggest that these individuals have accelerated skeletal development . Some early studies attributed developmental deficiency to various factors such as malnutrition or genetics, but it has been alternatively suggested that dysfunction of the hypophysis and endocrinological system may also affect skeletal growth of children with orofacial clefts …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…En el caso particular del género masculino, estos presentaron diferencias significativas en el promedio de longitud durante casi toda la trayectoria desde el nacimiento hasta el primer año de vida; esto pudo ocurrir por la presencia de niños con talla alta o en el límite de ésta en los niños del grupo control, aumentando considerablemente el promedio de longitud de niños sin FLMP. Además, se ha reportado en la literatura una asociación entre la deficiencia de hormona de crecimiento y la presencia de FLMP, afectando en la estatura de estos niños/as, sin embargo esto debe estudiarse en cada individuo luego de descartar factores nutricionales que estén afectando en el crecimiento (Abdollahi-Fakhim et al, 2015 ).…”
Section: Discussionunclassified